PERLINDUNGAN HUKUM BAGI KREDITOR PADA KASUS KEPAILITAN PERUSAHAAN/KKKS MINYAK DAN GAS BUMI: Studi Kasus Kepailitan Antara PT. Global Pacific Energi Dengan KKKS PT. Golden Spike Energy Indonesia - Lousia Ester Beby S. (to-ra, 2020)
Oil and Gas Company / KKKS PT. Golden Spike Energy Indonesia was sued for bankruptcy byPT. Global Pacific Energy due to unpaid debt. The lawsuit begins with the PKPU process, thepeace agreement, the bankruptcy decision of the Commercial Court, the cassation decision, andthe PK decision. This research is normative juridical, by deciphering the Bankruptcy Law andrelated to legal theories in the practice of its implementation in connection with the position ofKKKS PT. Golden Spike Energy Indonesia, a party to the cooperation contract with theGovernment of the Republic of Indonesia. Such problems are subject to research, where creditorsare faced with zero-asset companies. The results showed that the lack of protection for creditorsin the Oil and Gas KKKS. Keywords: Bankruptcy; KKKS; Natural resources.